2022
DOI: 10.1007/s00402-022-04431-3
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict favourable quality of life after surgically treated vertebral osteomyelitis? Analysis of a prospective study

Abstract: Purpose Vertebral osteomyelitis (VO) is a severe clinical entity associated with significant morbidity and mortality. Several studies have showed that successful treatment of VO patients leads to significantly improved quality of life (QoL). Nevertheless, QoL levels of these patients remained below those of the general population. There are rarely studies focusing on predicting factors for favourable QoL after surgically treated VO. The aim of this study was to identify factors influencing positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…High preoperative leg pain (but not back pain) has previously been associated with unfavorable postoperative outcomes. 3 Our findings underscored the importance of recording preoperative leg pain in assessing the severity of SD.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…High preoperative leg pain (but not back pain) has previously been associated with unfavorable postoperative outcomes. 3 Our findings underscored the importance of recording preoperative leg pain in assessing the severity of SD.…”
Section: Discussionmentioning
confidence: 52%
“…A patient with a formal indication for surgery but who was already suffering from significant disability before the development of SD might be considered to not benefit from surgery. By contrast, another study by Yagdiran et al 3 showed that even patients with low preoperative QoL benefited from surgery in QoL.…”
Section: Quality Of Lifementioning
confidence: 85%
See 3 more Smart Citations